2009
DOI: 10.1145/1559755.1559761
|View full text |Cite
|
Sign up to set email alerts
|

Improving Chen and Han's algorithm on the discrete geodesic problem

Abstract: The computation of geodesic distances or paths between two points on triangulated meshes is a common operation in many computer graphics applications. In this article, we present an exact algorithm for the single-source all-vertices shortest path problem. Mitchell et al. [1987] proposed an O ( n 2 log n ) method (MMP), based on Dijkstra's algorithm, where n is the complexity of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
126
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(127 citation statements)
references
References 22 publications
0
126
0
1
Order By: Relevance
“…There are many existing methods for the calculation of a geodesic path. We use the method proposed by Xin et al [34], since it calculates the exact geodesic path that guarantees the non-intersection between each path. Although all these geodesic paths do not intersect with each other, they may have common points.…”
Section: Calculate Geodesic Paths Between the Bound Visual Verticesmentioning
confidence: 99%
“…There are many existing methods for the calculation of a geodesic path. We use the method proposed by Xin et al [34], since it calculates the exact geodesic path that guarantees the non-intersection between each path. Although all these geodesic paths do not intersect with each other, they may have common points.…”
Section: Calculate Geodesic Paths Between the Bound Visual Verticesmentioning
confidence: 99%
“…We compares the FWP method with other representative geodesic algorithms, including MMP [2], ICH [7], PCH [8], FMM [13], [14], [22], the heat method [16] and the label correcting (LC) method [23]. We classify these algorithms in two groups, i.e., macro and micro.…”
Section: Comparisonmentioning
confidence: 99%
“…Xin and Wang [7] observed that the slow performance of the CH algorithm is mainly due to the large amount of useless windows processed. They proposed a simple yet effective window filter to detect the useless windows, accompanied by a priority queue for window organization.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Dijkstra's algorithm has been successfully applied in such fields [16] as operational research, computer science, geographic information science and transportation, etc.…”
Section: Dijkstra's Algorithmmentioning
confidence: 99%
“…Based on this insight, this essay makes an attempt to apply Dijkstra's algorithm [14][15][16][17] which settles the shortest path problem of the graph theory to the energy conservation optimization of the main cutting edge curve of the twist drill. A specific method used in determining the main cutting edge curve in the helicoid rake face of the twist drill that minimizes the drilling power is introduced.…”
Section: Introductionmentioning
confidence: 99%